Relationship between Supply Chain Management Effects on the Tax Information System and Willingness to Pay Taxes - Vitra Yozi; Sri Mulyani; Citra Sukmadilaga; Hamdi A Pertama (International Journal of Supply Chain Management, 2019)
Abstract- The main purpose of this study paper was to examine whether user satisfaction of the tax information systems can increase willingness to pay taxes. We investgated the supply chain management effects on the performance of the tax payment for eller and the user. So we surveyed 234 taxpayers in 16 tax offices in Indonesia. The data were analysed using structural equation modelling. The result showed that the higher user satisfaction on the tax information systems were associated with the greater willingness of taxpayer to pay tax. The findings of this study can be contribute as a premise that can form the basis for further research in the field of technology and tax compliance issues.